Problems facing university students during Corona pandemic - Rihab Ahmad Banisaeed; Mohammad Omar Al-Momani (Institute of Advanced Engineering and Science, 2023)
University students face many problems and difficulties that hinder their academic and scientific careers. The researchers, in various locations, seek to find solutions to them, especially in light of the global pandemic of Corona, which has exacerbated these problems. Therefore, this study aimed to identify the problems facing university students at Al-Balqa Applied University in Jordan during the Corona pandemic from their viewpoints. Also, this study aimed to identify the relationship between these problems and some variables, such as gender, type of major and academic degree. The researcher used the descriptive approach and developed a questionnaire. The study sample comprised 700 male and female students in the second semester of the academic year (2021/2022). The study concluded that the students’ levels of problems got a high degree in all domains and on the instrument as a whole. Besides, there were statistically significant differences following the gender variable in favor of males. The study concluded that there were statistically significant differences following the type of academic major variable and in favor of students of scientific majors. There were no statistically significant differences due to the student’s academic degree variable (intermediate diploma, bachelor’s degree).